EFFECT OF AUXILIARY VIBRATION INFLUENCE ON ELECTRO STIMULATION PROCEDURE EFFICIENCY USING HUMAN SKIN IMITATOR - M. G. Kiselev; E. I. Labun; P. S. Liutsko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The experimental complex of apparatus of electrical stimulation with combination of active electrode vibration of original design was developed. It has a possibility to use various mechanical and electrical parameters of vibration influence and electrical stimulation. In particular it has a possibility to apply various directions of vibrations to an active electrical stimulation electrode. The results of experiments have shown that the use of vibration-combined electrical stimulation procedure has an advantage in efficiency over traditional non-vibrating regime of procedure. Moreover, percussive-frictional mode is superior due to opportunities it has to change the modes of action.